EFL Islamic Elementary Students’ Anxiety in Learning English - Leffi Noviyenti (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study investigates elementary school students’ anxiety over learning English, the influential factors of their anxiety, and the teacher’s strategies to reduce their anxiety. Anchored in a mixed research method, 75 fifth grade students at SDIT Robbi Rodhiyah in Curup, Bengkulu, Indonesia were involved as the sample for quantitative investigations into their learning anxiety levels and the influential factors of their anxiety. In addition, one English teacher was recruited as the qualitative subject to be interviewed on the teacher’s strategies to reduce students’ anxiety. The quantitative investigations deployed the FLCAS questionnaire developed by Horwitz, and the qualitative investigation conducted interviews with the English teacher. Descriptive statistics were employed to analyze questionnaire data, and an interactive model was undertaken to analyze interview data. The results revealed that the students were at a high level of English learning anxiety. Their anxiety stemmed from some factors such as anxiety over tests, fear of negative evaluation, and communication apprehension. In efforts to help students cope with and reduce their English learning anxiety, the teacher applied some strategies such as relaxation, music and laughter, self-encouragement, and additional considerations resting upon students’ to help them reduce their anxiety.